Analysis of synonymous codon usage in Zea mays - Liu, Hanmei; He, Rui; Zhang, Huaiyu; Huang, Yubi; Tian, Mengliang; Zhang, Junjie (Molecular biology reports, 2010)
It is important and meaningful to understand the codon usage pattern and the factors that shape codon usage of maize. In this study, trends in synonymous codon usage in maize have been firstly examined through the multivariate statistical analysis on 7402 cDNA sequences. The results showed that the genes positions on the primary axis were strongly negatively correlated with GC3s, GC content of individual gene and gene expression level assessed by the codon adaptation index (CAI) values, which indicated that nucleotide composition and gene expression level were the main factors in shaping the codon usage of maize, and the variation in codon usage among genes may be due to mutational bias at the DNA level and natural selection acting at the level of mRNA translation. At the same time, CDS length and the hydrophobicity of each protein were, respectively, significantly correlated with the genes locations on the primary axis, GC3s and CAI values. We infer that genes length and the hydrophobicity of the encoded protein may play minor role in shaping codon usage bias. Additional 28 codons ending with a G or C base have been defined as “optimal codons”, which may provide useful information for maize gene-transformation and gene prediction.